2002
DOI: 10.1152/ajpendo.00381.2001
|View full text |Cite
|
Sign up to set email alerts
|

Peptide transport in the mammary gland: expression and distribution of PEPT2 mRNA and protein

Abstract: The lactating mammary gland utilizes free plasma amino acids as well as those derived by hydrolysis from circulating short-chain peptides for protein synthesis. Apart from the major route of amino acid nitrogen delivery to the gland by the various transporters for free amino acids, it has been suggested that dipeptides may also be taken up in intact form to serve as a source of amino acids. The identification of peptide transporters in the mammary gland may therefore provide new insights into protein metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
50
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 43 publications
4
50
0
Order By: Relevance
“…In the lung, PEPT2 is expressed in type II pneumocytes and in the apical membrane of tracheal and bronchial epithelial cells (31). Furthermore, a recent study has shown the localization of PEPT2 in the apical membranes of the epithelial cells of the terminal duct and glandules as well as the main and segmental ducts in the lactating mammary gland (30). By RT-PCR, expression of PEPT2 mRNA was also demonstrated in the spleen, colon, and pancreas (20).…”
Section: Tissue Distribution Of Pept1 and Pept2 And Their Tubular Locmentioning
confidence: 96%
See 1 more Smart Citation
“…In the lung, PEPT2 is expressed in type II pneumocytes and in the apical membrane of tracheal and bronchial epithelial cells (31). Furthermore, a recent study has shown the localization of PEPT2 in the apical membranes of the epithelial cells of the terminal duct and glandules as well as the main and segmental ducts in the lactating mammary gland (30). By RT-PCR, expression of PEPT2 mRNA was also demonstrated in the spleen, colon, and pancreas (20).…”
Section: Tissue Distribution Of Pept1 and Pept2 And Their Tubular Locmentioning
confidence: 96%
“…Although PEPT1 is found in the intestine and in bile duct epithelium (36,47), in these locations it does not contribute to the clearance of diand tripeptides from the circulation. PEPT2 has been localized to the apical membrane of tracheal and bronchial epithelial cells in the lung (31) and ductal cells of the lactating mammary gland (30), but by this localization PEPT2 cannot also play a role in the clearance of short-chain peptides from the blood. Functional studies using isolated choroid plexus suggest that PEPT2 there is located in the apical membrane, where it may mediate the removal of di-and tripeptides from the cerebrospinal fluid to the blood (46) rather then serving as an import system.…”
Section: Integrating the Peptide Transporters Into Overall Amino Acidmentioning
confidence: 99%
“…Pept2 mRNA is expressed in specific cell types of the brain, including astrocytes, subependymal cells, and ependymal cells, and Pept2 protein is detected along the apical membrane of epithelial cells of the choroid plexus (Table 5) (Berger and Hediger, 1999;Shu et al, 2002). Pept2/PEPT2 mRNA and/or protein are also expressed in the enteric nervous system, colon, liver, pancreas, lungs, nasal mucosa, and mammary glands (Groneberg et al, 2001(Groneberg et al, , 2002Zhang et al, 2004a;Bahadduri et al, 2005;Ruhl et al, 2005;Lu and Klaassen, 2006;Quarcoo et al, 2009).…”
mentioning
confidence: 99%
“…PEPT2 is present at the apical membrane of choroidal plexus epithelial cells and may function in the efflux of peptides across the blood-brain barrier from cerebrospinal fluid to blood (Shu et al, 2002). In mammary gland epithelia, PEPT2 is thought to be involved in the reuptake of small peptides that accumulate from the hydrolysis of milk proteins (Groneberg et al, 2002). PEPT2 is located in alveolar type II pneumocytes, bronchial epithelium, and endothelium of small vessels (Groneberg et al, 2001) and thought to be responsible for uptake of di-and tripeptides in the lung (Groneberg et al, 2001).…”
mentioning
confidence: 99%